Comparative Study on the Clinical Efficacy and Safety of Acitretin and MTX in the Treatment of Pustular Psoriasis by TLR7/MyD88/CXCL16 Pathway - Jiajing Lu; Yu Wang; Ying Li; Yu Gong; Yangfeng Ding; Yuling Shi (Applied Bionics and Biomechanics)
Objective. To investigate the clinical efficacy and safety of acitretin and MTX with TLR7/MyD88/CXCL16 in the treatment of pustular psoriasis. Method. A total of 54 patients with pustular psoriasis were randomly divided into control group (n=14) and study group (n=40). MTX was used in the control group, and different doses of acitretin were used in the study group, which were divided into low-dose group (n=13), medium-dose group (n=13), and high-dose group (n=14). Symptom relief time, recurrence rate, GPPASI improvement rate, treatment response rate, BSA, DLQI score, and TLR7 and CXCL16 levels were compared among four groups. Result. The erythema, fever, and pustules disappeared in the low-dose group, the medium-dose group, and the high-dose group for a shorter time than control group, and it is shortest for the high-dose group. The low-dose, medium-dose, and high-dose groups had relatively lower recurrence rates at 1 month and 3 months (P<0.05). The improvement rates of GPPASI50 of the four groups (the control group, low-dose group, medium-dose group, and high-dose group in turn) were 71.4%, 78.3%, 80.2%, and 80.8%; GPPASI75 of the four groups were 73.5%, 74.3%, 79.4%, and 80.9%; and GPPASI90 were 12.9%, 13.1%, 13.4%, and 13.8%. After treatment, the BSA and DLQI scores of the four groups were reduced. The BSA and DLQI scores of the study group decreased more significantly, and the high-dose group had the most significant improvement (P<0.05). The incidence of adverse reactions in the four groups was 16.2%, 8.1%, 10.3%, and 14.7%, respectively. The high-dose group had a higher incidence of adverse reaction than the low-dose group (P<0.05). The effective rates of treatment of the four groups were 69.1%, 86.9%, 88.2%, and 91.9%, respectively. The study group had higher treatment efficiency than the control group, and the high-dose group had the highest treatment efficiency (P<0.05). After treatment, the level of serum TLR7 and CXCL16 was significantly reduced, but which in the study group decreased more significantly (P<0.05). Conclusion. The clinical effect of a high dose of acitretin on pustular psoriasis is remarkable. It can reduce the recurrence rate and improve the quality of life and clinical symptoms. Therefore, a high dose of acitretin is worth popularizing and applying.